2011
DOI: 10.3171/2010.5.jns08914
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid supplementation and reduction of traumatic axonal injury in a rodent head injury model

Abstract: Dietary supplementation with a fish oil concentrate rich in the O3FAs EPA and DHA increases serum levels of these same fatty acids in a dose-response effect. Omega-3 fatty acid supplementation significantly reduces the number of APP-positive axons at 30 days postinjury to levels similar to those in uninjured animals. Omega-3 fatty acids are safe, affordable, and readily available worldwide to potentially reduce the burden of traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 39 publications
4
101
1
Order By: Relevance
“…By modifying the Marmarou weight-drop model of concussion, we have been able to diminish impact forces to effect no obvious reaction or behavior change, and thus simulating less than a concussive injury. 2,[51][52][53] Using staining for amyloid precursor protein, we have shown that these subconcussive impacts reliably produce tearing of axons and the formation of axonal retraction bulbs in the brainstem-level descending motor pathways. In reducing the fall height of a 450-g mass from 2 to 1 m, we found no alteration of consciousness or responsiveness but significant numbers of amyloid precursor protein-positive axons compared with the number in controls (JD Mills, JE Bailes, unpublished data, 2010).…”
Section: Laboratory Evidence Of Subconcussive Effectsmentioning
confidence: 97%
“…By modifying the Marmarou weight-drop model of concussion, we have been able to diminish impact forces to effect no obvious reaction or behavior change, and thus simulating less than a concussive injury. 2,[51][52][53] Using staining for amyloid precursor protein, we have shown that these subconcussive impacts reliably produce tearing of axons and the formation of axonal retraction bulbs in the brainstem-level descending motor pathways. In reducing the fall height of a 450-g mass from 2 to 1 m, we found no alteration of consciousness or responsiveness but significant numbers of amyloid precursor protein-positive axons compared with the number in controls (JD Mills, JE Bailes, unpublished data, 2010).…”
Section: Laboratory Evidence Of Subconcussive Effectsmentioning
confidence: 97%
“…Docosahexaenoic acid (DHA), for example, is an omega-3 fatty acid that exhibits strong anti-inflammatory and neuroprotective effects 193 . In experimental models of TBI, DHA supplementation is known to reduce axonal damage in rodents 194 . This finding was recently supported in a clinical study of collegiate football players where prophylactic DHA supplementation significantly reduced serum levels of a known biomarker (Neurofilament Light; NFL) for axonal damage that was otherwise significantly elevated over the course of the season in athletes without DHA 195 .…”
Section: Nutritional Supplementationmentioning
confidence: 99%
“…Several studies support the use of oxygen-radical scavengers, steroids, neurotrophic factors, or dietary supplementation, 183,[190][191][192][193][194] Although each of these classes of agents shows various degrees of axonal protection, they, too, will require further development. In addition, other promising agents are in the pipeline, including erythropoietin and somatostatin, and these, too, will require detailed evaluation.…”
Section: Additional Therapeutic Approachesmentioning
confidence: 99%